2021
DOI: 10.21203/rs.3.rs-794174/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmembrane p24 Trafficking Protein 2 Regulates Inflammation Through the TLR4/NF-κB Signaling Pathway in Lung Adenocarcinoma

Abstract: Background: To investigate the role of transmembrane p24 trafficking protein 2 (TMED2) in lung adenocarcinoma (LUAD) and determine whether TMED2 knockdown could inhibit LUAD in vitro and in vivo.Methods: TIMER2.0, Kaplan-Meier plotter, gene set enrichment analysis (GSEA), Target Gene, and pan-cancer systems were used to predict the potential function of TMED2. Western blotting and immunohistochemistry were performed to analyze TMED2 expression in different tissues or cell lines. The proliferation, development,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This study found that by overexpression of miRNA-141, the expression of TLR4 and its signaling pathway-related proteins NF-kB, Rac1, and IL-1b in vascular tissues of thrombotic rats was significantly down-regulated, and by restoring the expression of TLR4 and NF-kB, the expression of Rac1 and IL-1b was restored at the same time, and multiple related indexes of miRNA-141 on thrombus were significantly reversed (80). Activated TLR4 induces late activation of NF-kB, which significantly increases TNF-a expression and causes widespread inflammation (53).…”
Section: Mirna-141mentioning
confidence: 81%
“…This study found that by overexpression of miRNA-141, the expression of TLR4 and its signaling pathway-related proteins NF-kB, Rac1, and IL-1b in vascular tissues of thrombotic rats was significantly down-regulated, and by restoring the expression of TLR4 and NF-kB, the expression of Rac1 and IL-1b was restored at the same time, and multiple related indexes of miRNA-141 on thrombus were significantly reversed (80). Activated TLR4 induces late activation of NF-kB, which significantly increases TNF-a expression and causes widespread inflammation (53).…”
Section: Mirna-141mentioning
confidence: 81%